296. Use of the gEUD in Philips Pinnacle3 TPS for prostate radiotherapy treatment plans optimization with VMAT technique. (December 2018) - Grimaldi, L.; Morandini, V.; Saiani, F.; Giancaterino, S.; De Martino, D.; Panese, A.; Berlinghieri, S.; Castrezzati, E.; Magnani, M.; Raspanti, D.; Pertutti, S.; Frata, P.
Abstract : Purpose: Aim of this study is to find a starting point for gEUD parameters[1] in the Philips Pinnacle 3 TPS to reach a comparable dose distribution to Target and saving as much as is possible the OARs irradiation in a prostate RT scheme. Methods and materials: For 10 patients who underwent to prostate radiotherapy, two RT plans were optimized using for both a VMAT technique. For the first plan only physical parameter were used, instead for the other the biological gEUD parameter were also used. The TPS was Philips Pinnacle 3 v9.10. Results: For the Targets the two plans show an equivalent dosimetry in term of Conformity Index ( COIN = ( ( V T, pi ) 2 / ( V T * V pi ), Homogeneity Index ( HI = 100 * ( D 2 % - D 98 % ) / D pi ) and Gradient Index ( GI = V 50 % / V 100 % ) . Instead for the principals OARs, while the bladder and the femoral heads don't put in evidence substantial differences, for the rectum there is a significant decrease of absorbed dose. To optimize a VMAT plan by using the Pinnacle 3 radiobiological function and obtain a dose distribution comparable to that based on a physical optimization, the following parameters have been set: When using VMAT optimization based on the gEUD, the following differences emerge: the programmed number of MU increases by over 40%; on average, the side of the equivalent square field decreases by more than 13%; the absorbed dose at the middle and lower levels of the rectum is halved. Conclusions: The assumption that a normal tissue responds in serial manner leads to lack of control over the low- and mid-dose range, as the risk of complications is predominantly determined by the high doses. The optimization with cost functions based on the gEUD concept is straightforward and numerically expedient.